Modelamiento estadístico para la predicción analógica del proceso de inyección de agua en yacimientos de la cuenca del Valle Superior del Magdalena (2012)
The project development is based on the analysis of the waterflooding process historical performance in the Upper Magdalena Valley Basin; from them, the static and dynamic properties are compiled, organized and examined per block in each field submitted to that kind of improved recovery method, in such a way that is possible to discriminate the incremental production of oil and water and to identify the process stages with the aim of constructing a secondary production database. After that, the Bush & Helander prediction method is modified to extract from the database a set of parameters whose performance is evaluated by fitting the probability distribution to a function that best describes the behavior, this allows the generation of a statistical and analogical prediction method.